Weichselian permafrost depth in the Netherlands: A comprehensive uncertainty and sensitivity analysis: - Govaerts, J.; Beerten, K.; Veen, J. ten (Copernicus GmbH, 2016)
The Rupelian clay in the Netherlands is currently the subject of a feasibility study with respect to the storage of radioactive waste in the Netherlands (OPERA-project). Many features need to be considered in the assessment of the long-Term evolution of the natural environment surrounding a geological waste disposal facility. One of these is permafrost development as it may have an impact on various components of the disposal system, including the natural environment (hydrogeology), the natural barrier (clay) and the engineered barrier. Determining how deep permafrost might develop in the future is desirable in order to properly address the possible impact on the various components. It is expected that periglacial conditions will reappear at some point during the next several hundred thousands of years, a typical time frame considered in geological waste disposal feasibility studies. In this study, the Weichselian glaciation is used as an analogue for future permafrost development. Permafrost depth modelling using a best estimate temperature curve of the Weichselian indicates that permafrost would reach depths between 155 and 195ĝ€m. Without imposing a climatic gradient over the country, deepest permafrost is expected in the south due to the lower geothermal heat flux and higher average sand content of the post-Rupelian overburden. Accounting for various sources of uncertainty, such as type and impact of vegetation, snow cover, surface temperature gradients across the country, possible errors in palaeoclimate reconstructions, porosity, lithology and geothermal heat flux, stochastic calculations point out that permafrost depth during the coldest stages of a glacial cycle such as the Weichselian, for any location in the Netherlands, would be 130-210ĝ€m at the 2 σ level. In any case, permafrost would not reach depths greater than 270ĝ€m. The most sensitive parameters in permafrost development are the mean annual air temperatures and porosity, while the geothermal heat flux is the crucial parameter in permafrost degradation once temperatures start rising again.